Hak-Hak dan Perlindungan Hukum Terhadap Pemegang Saham Minoritas Akibat Merger pada Bank Syariah Indonesia - R Dinan Rayan Makhfirah (CV. Syntax Corporation Indonesia, 2022)
Merger is one of the ways used by banks in Indonesia to expand their business, increase capital and create banking synergies which are business strategies in the future. This action must be taken through the General Meeting of Shareholders (GMS). Participants in the General Meeting of Shareholders (GMS) are the Shareholders, Commissioners and Directors. In reality, in a company that is already in the form of a company, shareholders will be divided into two types when viewed from the composition of share ownership, namely majority shareholders and minority shareholders. The interests of the dominant or majority shareholder and the minority shareholder in running the company's business are often inconsistent with one another. If in the General Meeting of Shareholders (GMS) there is a difference of opinion between the majority shareholder and the minority shareholder and the decision-making mechanism is the largest vote based on the most shares, the minority shareholder will always lose compared to the majority shareholder. This is very detrimental to minority shareholders because their goals and objectives are not achieved because they are defeated by the voting system based on the majority of shares. Therefore, minority shareholders need to be protected. The type of research used in this research is normative juridical. Sources of data used are secondary data consisting of primary, secondary, and tertiary legal materials. The data collection technique used in this research is library research. The rights of minority shareholders are personal rights, appraisal rights, preemptive rights, enquette rights, and derivative rights. There are two forms of legal protection, namely preventive and repressive. A form of preventive protection, namely legal protection given to minority shareholders, especially public limited liability companies. Preventive protection is protection to prevent disputes. In this preventive protection, legal subjects are given the opportunity to submit their objections or opinions before a government decision gets a definitive form. While repressive legal protection aims to resolve disputes that occur in the community in order to achieve a fair settlement. The handling of legal protection by general courts and administrative courts in Indonesia belongs to this category of legal protection